Pemanfaatan Minyak Bekas Goreng dan Limbah Kopi sebagai Lilin Aromaterapi untuk Meningkatkan Minat Belajar Kimia Siswa di SMAN 2 Pontianak - Prawiranti, Yulizar; Weni Mandasari; Delta Fenisa; Muftiah Yasi Dwi Wahyuni; Elpe Bibas; Fitriyan Kurnia; Pratika Linanda (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
This service program aims to increase students' interest in chemistry lessons through contextual activities, namely making aromatherapy candles from used cooking oil and coffee. This activity responds to the challenge of students' low understanding of chemistry concepts and the lack of education on sustainable household waste management. The implementation was conducted in the form of interactive training to 12th grade science students at SMAN 2 Pontianak, combining demonstration with hands-on practice. Pre-Test results showed an average initial understanding of 89.63%, then significantly improved after the training, with 93% of participants reaching the excellent category. Satisfaction surveys showed positive responses to the quality of learning and guidance provided. This activity was able to bridge chemical theory with real applications, as well as introduce circular economy principles in a simple way. The impact of the activity includes increased understanding, appreciation of chemistry, and environmental awareness. This activity has the potential to be implemented in other schools as a practice-focused learning method.